DINAMIKA KINERJA PEMASARAN: ANALISIS PERAN MARKETING CAPABILITY, ENTREPRENEURIAL MARKETING, DAN SOCIAL MEDIA MARKETING - Muhammad David Firmansyah; Ali Ali (Universitas Dharmawangsa, 2026)
This study examines the declining marketing performance of furniture MSMEs in Jepara Regency, which is assumed to be influenced by marketing capability, entrepreneurial marketing, and social media marketing, as well as the mediating role of product innovation. The objective is to analyze the effect of these three variables on marketing performance with product innovation as a mediator. A quantitative descriptive approach was used with furniture MSMEs in Jepara Regency as the research object. Primary data were collected through questionnaires distributed to respondents. The population consisted of 3,945 MSMEs, and 98 samples were selected using purposive sampling and the Slovin formula. Data were measured using a 1–5 Likert scale and analyzed using the Partial Least Square (PLS) method with SmartPLS 3. The results show that marketing capability, entrepreneurial marketing, and social media marketing have a positive and significant effect on marketing performance and product innovation. Furthermore, product innovation significantly mediates the relationship between these variables and marketing performance